Hubungan Antara Kesiapan Keluarga dengan Resiko Kegawatan di Masyarakat Sebagai Upaya Perwujudan Desa Siaga - Yuliansari, Pratiwi; Sumirat, Widhi (The Indonesian Journal of Health Science, 2024)
An emergency is a situation that occurs suddenly and can cause illness or injury, if proper and quick treatment is not received, it can result in disability or even death. Everyday emergencies that are often encountered at home include heart attacks, bleeding, trauma and burns. Health problems that occur in the community require the government to collaborate with the community itself in managing the maintenance of a healthy country through the alert village program. This research aims to determine the relationship between family preparedness and the risk of emergencies occurring in the community as an effort to increase village alertness. Method: This research was conducted using a cross sectional study approach. The total research sample was 40 respondents determined by purposive sampling consisting of cadres in Darungan Village. Data collection was carried out using a questionnaire that had been modified through previous validity and reliability tests regarding family readiness and home security in dealing with emergencies at home. Research data was analyzed using the Pearson correlation test. The research results show that family preparedness is related to the risk of emergencies with a significance value of 0.000. The coefficient interval for family readiness in predicting the risk of emergencies has a strong relationship level, namely 0.688 or 68%, this means that families who are prepared have a minimum risk in dealing with emergency conditions within the household. The risk of an emergency occurring in society can be overcome by being aware of the family's own preparedness. All family members need to be well prepared in dealing with emergencies that can occur at home at any time. Houses are the main and first indicator for creating an alert village so that community health can be achieved as a whole. Keywords: Family Readiness, Emergency at Home, Alert Village